Creation and validation of a web-based diabetic retinopathy screening training module for Filipino health students and professionals - Santiago, Darby E.
This capstone project developed and evaluated a 2–4-hour web-based training course to improve health students’ and professionals’ proficiency and confidence in classifying fundus photographs for DR screening. The course, which utilized Google Classroom as its LMS platform, integrated video lectures, formative quizzes, and a summative exam to teach retinal anatomy, DR retinal lesions, and fundus photo classification. The course contained six modular units (20-25 minutes each) which covered normal retinal anatomy, DR lesion recognition, and referral criteria using a standardized checklist. A total of 7 video lectures (total running time: 34 minutes) used YouTube and EdPuzzle for interactive, self-paced learning. Formative assessments included two quizzes, and a 15-image practice set with instant feedback. The final assessment was a 50-image exam (15 normal, 20 mild/moderate DR, 10 severe DR, 5 macular edema) that effectively evaluated the capacity of the learners to classify those with DR and those without. There were 60 learners who participated, all of whom were medical students (87% Gen Z, 13% Millennials). The pre-course survey revealed low baseline confidence: 60% lacked confidence in assessing fundus photo quality; 76.7% lack confidence in interpreting fungus photos; while only 16.7% said that they can identifying key signs of DR. However, as they watched the videos, their knowledge base and confidence seemed to have increased as reflected in the results of their quizzes (94.6% got a perfect score in Quiz 1 and 71.2% got perfect score in quiz 2), practice set (49.1% achieved perfect score after retakes), and the final exam (where 80% scored >90% initially; after retakes, 98% met proficiency). Post-course evaluations showed 100% agreement that lectures aligned with objectives and improved the learners’ understanding of the topics. They praised the clinically relevant photos and the scaffolded approach but requested more photos, more examples of lesions and “artifacts.” The key strengths of this capstone project are that (1) 84% of the learners completed the course in less than 4 hours; (2) the assessment retakes and instant feedback reinforced learning (mastery); and (3) the final exam results showed that the learning module was highly effective in teaching the skill of distinguishing diabetic retinopathy fundus photos from normal.